Which is the better timing between embolization and surgery for hypervascular spinal tumors, the same day or the next day?: A retrospective comparative study. Issue 23 (June 2018) - Tang, Benqiang; Ji, Tao; Guo, Wei; Tang, Xiaodong; Jin, Long; Dong, Sen; Xie, Lu
Abstract : Abstract: Previous series presented the timing between embolization and surgery in a wide range on the basis of their experience rather than supportive data. And comparative studies were limited to small samples. In addition, there is no study publishing the timing by considering both safety and efficacy of embolization. The aim of this study was to determine the better timing (the same day or the next day) between embolization and surgery for hypervascular spinal tumors by assessing the safety and efficacy of embolization. One hundred twenty-five embolizations with subsequent 120 operations for hypervascular spinal tumors between January 2010 and April 2013 were retrospectively reviewed. The time between embolization and surgery was mainly determined by interventional radiologist schedules and operating room available. Major complications of embolization were documented. The efficacy of embolization was compared between the same day and the next day group. Of the 125 embolizations, there were 4 major complications, all of which occurred on the same day of procedure. Of the 120 operations, 36 cases were operated on the same day of embolization, 74 on the next day, and 10 on the second day. When comparing the efficacy of embolization between the same day and the next day group, intraoperative blood loss (1483 ± 1475 vs 1548 ± 1099 mL, P  = .80), intraoperative transfusion requirement (1011 ± 1200 vs 1112 ± 890 mL, P  = .62), and postoperative blood loss (1146 ± 933 vs 1031 ± 777 mL, P  = .50) were not significantly different. Embolization carries certain risks (4/125, 3.2%) for major complications, which may occur within the time window of 1 day. Two patient groups showed no difference on the efficacy of embolization. Operation should be scheduled on the next day of embolization if possible.